Factibilidad para la Implementación de una Empresa Productora y Comercializadora de Crema Hidratante a Base de Aloe Vera con Aceite de Almendras en la Ciudad de Loja - Tamay Coronel, Roxana Del Carmen (2016)
This research was conducted with the purpose of making a draft "FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY PRODUCES AND COMMERCIALIZES MOISTURIZER ALOE VERA BASED WITH ALMOND OIL IN THE CITY OF LOJA". For this reason the aim of this project is to conduct market research, technical, and financial support to provide a natural product and innovative added value such as aloe vera, also known as aloe vera, taking advantage of, skilled labor existing resources, raw material and thus contributing to the socio-economic development of the city of Loja. For studies of research methods and research techniques which were used to analyze the collected information and then make a specific study of the entire project was used, then it took into account the survey technique; the same that was applied to women in the city of Loja according to their social class, to implement the survey was calculated and a sample of 380 surveys were applied, and 17 bidders surveys that provide a range of similar products. In the study of market demand and supply we were analyzed to determine the host that has the product in the market. Resulting in an effective demand for 405,189 plaintiffs and unmet demand for zero year of 403,437 moisturizers. Then the technical study which took into account the installed capacity which determined that the company is in the ability to produce 73,000 moisturizers presentation of 50ml and whose capacity will be 23,920 units used moisturizers 50ml was performed; Likewise the size and location, plant layout, project engineering, organizational structure - functional, the constitution, organization and functions manuals, same that are critical to the implementation of a good organization. In the financial study it found that the project received an investment of $ 30,804.07 and will be financed with a contribution of partners 74.03% of the total investment which corresponds to $ 22,804.07 and a loan that will remain with the financial institution Ban-Ecuador will constitute 25.97% corresponding to $ 8000.00 to 5 year period to 11% annual interest. Financial evaluation indicators showed positive and encouraging results to ensure good profitability of the project where the Net (NPV) Present Value 25,434.16 dollars, Internal Rate of Return (IRR) 29.75%, Capital Recovery Period calculated ( PRC) 2 years, 6 months and 18 days cost Benefit ratio (RBC) 0.12 cents, and sensitivity analysis for the increase in costs is 4.44%, and decreased income is 3, 96% Subsequently it concluded that there is the feasibility of creating the producing and trading company based moisturizer with aloe vera almond oil in the city of Loja: since according to the results it was determined that the project is feasible. Finally, conclusions, recommendations, bibliography and appendices are presented.